2009
DOI: 10.1002/mnfr.200800504
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation prevents the inhibition of myogenic differentiation in oxidatively injured C2C12 murine myoblasts

Abstract: Creatine (Cr), one of the most popular nutritional supplements among athletes, has been recently shown to prevent the cytotoxicity caused by different oxidative stressors in various mammalian cell lines, including C2C12 myoblasts, via a direct antioxidant activity. Here, the effect of Cr on the differentiating capacity of C2C12 cells exposed to H(2)O(2) has been investigated. Differentiation into myotubes was monitored using morphological, ultrastructural, and molecular techniques. Treatment with H(2)O(2) (1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 80 publications
(98 reference statements)
7
92
1
2
Order By: Relevance
“…The overexpression of PGC-1 in the skeletal muscle of aged mice improves oxidative capacity, suppresses mitochondrial degradation, and prevents muscle atrophy [94]. Building on our group's previous research in this area [95,96], we have recently studied the role of PGC-1 in C2C12 myoblasts subjected to oxidative stress during the early stages of differentiation, as well as the effect of H 2 O 2 (0.3 mM) on PGC-1 expression and its relationship with AMPK activation. We found that 1 h treatment with H 2 O 2 causes mitochondrial fragmentation and a mild mitochondrial impairment with a consequent marked increase in PGC-1 mRNA expression, as described by Kang et al [97] and Irrcher et al [98].…”
Section: Decreased Mitochondrial Dynamics and Quality Control Eventsmentioning
confidence: 98%
“…The overexpression of PGC-1 in the skeletal muscle of aged mice improves oxidative capacity, suppresses mitochondrial degradation, and prevents muscle atrophy [94]. Building on our group's previous research in this area [95,96], we have recently studied the role of PGC-1 in C2C12 myoblasts subjected to oxidative stress during the early stages of differentiation, as well as the effect of H 2 O 2 (0.3 mM) on PGC-1 expression and its relationship with AMPK activation. We found that 1 h treatment with H 2 O 2 causes mitochondrial fragmentation and a mild mitochondrial impairment with a consequent marked increase in PGC-1 mRNA expression, as described by Kang et al [97] and Irrcher et al [98].…”
Section: Decreased Mitochondrial Dynamics and Quality Control Eventsmentioning
confidence: 98%
“…Theoretically, if GAA metabolism remains undisturbed and/or low-to-modest quantities of exogenous GAA have been provided, a cumulative effect of the intervention might be neutral or antioxidant protection through creatineand arginine-driven medium. Creatine, the end product of GAA utilization, is thought to have antioxidant capacity in some studies (Sestili et al 2006;Sestili et al 2009), but reduce antioxidant status in others (Percário et al 2012). According to Fathi and Tanha (2015), arginine supplementation increased plasma GPx activity and decreased MDA level in the broiler with cold-induced acites.…”
Section: Antioxidant Capacity and Enzyme Activitymentioning
confidence: 99%
“…The murine C2C12 cells were cultured as previously described (23). During C2C12 differentiation, cells were harvested by trypsinisation in proliferative phase (myoblasts 60-70% confluence), upon reaching confluence (T0) and in the following four days of differentiation (T1, T2, T3 and T4).…”
Section: Cell Culturementioning
confidence: 99%